IMPLEMENTASI PERATURAN MENTERI PERHUBUNGAN NOMOR 60 TAHUN 2021 TENTANG PERUBAHAN KEDUA ATAS PERATURAN MENTERI PERHUBUNGAN NOMOR 104 TAHUN 2017 TENTANG PENYELENGGARAAN ANGKUTAN PENYEBERANGAN PADA JASA PENYEBERANGAN KEMPANG DI KABUPATEN KEPULAUAN MERANTI TAHUN 2020-2021 - Riska Mawarni; Zulfikar Jayakusuma; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Minister of Transportation Regulation Number 60 of 2021 concerning the Second Amendment to the Regulation of the Minister of Transportation Number 104 of 2017 concerning the Implementation of Crossing Transportation in Meranti Islands Regency, there is a crossing transportation, namely the Kempang, Based on the phenomenon that researchers found that the standard of safety support facilities at the Kempang crossing in Tebing District was still low Height, such as the lack of seats for passengers, the absence of buoys for safety, if an accident occurs, does not comply with the applicable rules, it occurs due to a lack of supervision, the Meranti Islands Regency government should try to reinforce sanctions and carry out regular supervision.This research is a sociological research, namely research conducted by identifying the law and how the effectiveness of this law applies in society. This research is also based on primary data, name ly data obtained directly through observation and interviews.From this research, it can be concluded that the first implementation of Ministerial Regulation Number 60 of 2021 concerning the Second Amendment to the Regulation of the Minister of Transportation Number 104 of 2017 concerning the Implementation of Crossing Transportation on the Kempang crossing service in the Meranti Islands Regency, the two factors that hinder the implementation of the implementation of the Ministerial Regulation Number 60 of the Year 2021 Regarding the Second Amendment to the Regulation of the Minister of Transportation Number 104 of 2017 concerning the Implementation of Crossing Transportation on the Kempang Crossing Service in the Meranti Islands Regency, third, the efforts that the Meranti Islands Regency government can take so that the Minister of Transportation Regulation Number 60 of 2021 concerning the Second Amendment of the Minister of Transportation Regulation Number 104 of 2017 concerning the implementation of ferry transportation can be carried out at the kempang crossing in the Meranti Islands Regency. Keywords: Kempang-safety-cruise